복강경 담낭절제술시 기복증 유도전 복강내 Lidocaine 점적주입이 술 후 통증과 술 중 혈압 변화에 미치는 영향 - 송선옥; Sun Ok Song; 박소영; So Young Park; 김흥대; Heung Dae Kim; 윤성수; Sung Soo Yun; 이선영; Seon Young Lee; 김세연; Sae Yeon Kim; et al. (Korean journal of anesthesiology, 2002)
Background: This study was performed to evaluate the effects of pre-emptive subdiaphragmatic instillation of lidocaine before pneumoperitoneum on postoperative pain following a laparoscopic cholecystectomy (LC) and also to evaluate it`s effect on the chan